2014
DOI: 10.1111/cas.12538
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin‐induced severe hypersensitivity reaction: Role of IgE‐dependent basophil activation and FcεRI

Abstract: Basophil activation was observed in patients with a history of carboplatin-induced severe hypersensitivity reaction (HR). However, the precise mechanism by which carboplatin induces basophil activation and the associated surrogate markers remains to be elucidated. To investigate whether IgE-dependent mechanisms, including the overexpression of FcεRI, participate in carboplatin-induced basophil activation, 13 ovarian cancer patients were enrolled: 5 with a history of carboplatin-induced severe hypersensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 31 publications
(37 reference statements)
3
17
0
2
Order By: Relevance
“…The BRCA status of our patients was not available for further analysis in this retrospective study. However, basophil activation has been observed in patients with a history of severe carboplatin hypersensitivity reaction (Iwamoto et al, 2014 ). Whether, BRCA 1/2 and HRD-related genes modulate Th2 gene expression and increase specific IgE to carboplatin is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The BRCA status of our patients was not available for further analysis in this retrospective study. However, basophil activation has been observed in patients with a history of severe carboplatin hypersensitivity reaction (Iwamoto et al, 2014 ). Whether, BRCA 1/2 and HRD-related genes modulate Th2 gene expression and increase specific IgE to carboplatin is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Data analysis was performed by FlowJo (TreeStar, Ashland, OR, USA). BAT was considered positive when there was an SI ≥2 and/or a basophil activation percentage > 2% [16,17,[19][20][21]. We compared basophil activation percentage and SI (for CD63 and CD203c expression) between patients and controls.…”
Section: Cd203cmentioning
confidence: 99%
“…BAT has also been studied as a possible diagnostic method, given the role of basophils and mast cells as key cells in immediate hypersensitivity reactions. Viardot-Helmer et al [15] found an increased expression of CD63 with exposure to cisplatin; Iwamoto et al [16][17][18] and Jean-Luc [19] detected increased expression of the CD203C marker after incubation with carboplatin and oxaliplatin, respectively; Giavina-Bianchi et al [20] evaluated CD63 and CD203c expression in patients submitted to rapid drug desensitization (RDD) with oxaliplatin and carboplatin, obtaining positive results in 73% of patients. Due to the existing limitations of skin tests, further studies are essential to ascertain the role of the in vitro diagnostic methods, particularly BAT, in hypersensitivity reactions to platinum compounds, as well as to make comparisons with controls in order to gain a better understanding of the underlying immunological mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…They arise in up to 26.7% of patients and skin testing has been successfully performed although safety concerns exist regarding severe side-effects for the patient and risk of exposure of the medical personnel (Markman et al, 1999 ; Leguy-Seguin et al, 2007 ; Sugimoto et al, 2011 ). Consequently, the potential of BAT for predicting DHRs has been investigated using flow cytometric determination of CD203c (Iwamoto et al, 2012 , 2014 ). These authors verified the involvement of IgE in carboplatin-induced DHR, as the basophil activation could be inhibited by wortmannin and anti-IgE pretreatment by omalizumab.…”
Section: Bat For the Evaluation Of Immediate Drug Hypersensitivity Tomentioning
confidence: 99%